Pemberdayaan Masyarakat Peternak Kambing Melalui Disemenasi Feed Additive Daun Gamal di Desa Klungkung, Kabupaten Jember - Soliha Hani, Evita; Ridjal, Julian Adam; Utami, Ratih Apri; Ibanah, Indah; Yulianto, Roni; Widuri, Laily Ilman; Alfarisy, Fariz Kustiawan (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
ood security is a national issue including the production of quality ruminants. The main problem in this case is the low quality of animal feed and climate change factors that feed availability is inadequate. Feed additive technology is one of solution to produce feed with high nutritional. The aim of this activity is to empower the community to downstream technology through the introduce of gamal leaf feed additive technology. The location is located in Klungkung Village, Sukorambi District, Jember Regency. The first step carried out was socialization and training on making feed additives on gamal leaves to ensure the quality and availability of additive feed. The implementation used in this acitivy is community participation and training. To find out the achievements of this socialization activity, a pre-test and post-test were made regarding farmers' understanding of the gamal leaf feed additive. The results of this community service activity show an increase in knowledge regarding gamal leaf feed additive technology from 20% to 100%. The implementation of socialization and training on making feed additives from gamal leaves went well, community participation was very good as reflected in the presence of breeders until the end of the activity in a condition of constant numbers and active discussions.